Commercial-Off-the-Shelf-Technology in UK Military Training. (February 2016) - Curry, John; Price, Tim; Sabin, Phil
Aim. This article gives an overview of how commercial computer game technology was introduced for training, education and decision support within the British Army. Value of the article. It records the narrative of the introduction and development of first person shooter computer games into the British Army; an area where developments are not routinely reported outside the closed world of defence training. Methodology. The research was based on interviews of key staff who worked in procurement at the Defence Academy of the UK and for the MoD during 2002 to 2012. The interviewees included two officers, an experienced defence contractor and a senior civil servant. These interviews were given on the understanding that the views expressed would not be individually attributable as they might not represent those of their current employers. The authors were also given access to a unique collection of documents, some of which were not publically available, but are held in the archives of the UK Defence Academy. These are cited in the bibliography. Limitations of the article. This article cites the evidence from the time that supported the continued use of what was a radical and contentious new way of training. Since the introduction of Virtual Battle Space 2 into the British Army, further research into the effectiveness of games based training in the military has been published. Analysis. Games based training has become a significant part of the training cycle for many parts of the British Army. These games have limitations, but are the only alternative to real operations for some types of training. However, the difficult topic of what is the correct proportion of games based training to other types? is a contested area within defence training in the UK. Conclusions. Initial evaluations on the effectiveness of the use of computer games in preparing UK forces for operations in Iraq and Afghanistan showed they had a significant positive impact. The first experience of the British Army with these games has secured the long-term application of this technology and it is unrealistic to imagine future military training without some degree of games technology.